1998
DOI: 10.1002/etc.5620170702
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity effects of organosulfur compounds on anaerobic microbial metabolism

Abstract: Abstract-Four classes of organosulfur compounds were tested for their effects on anaerobic microbial activity as indicated by rates of lactate degradation, nitrate or sulfate reduction, and methanogenesis. Each class consisted of five to eight chemically related compounds that were added concurrently to anaerobic cultures established with an oily sludge inoculum. Effects on anaerobic activities were evaluated at different amounts of the chemicals and were concentration dependent in all cases. Thiophenes and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Our research showed that 50% inhibition of methanogenesis by methanethiol took place at concentrations between 7 and 10 mM for the substrates methanol, acetate, and hydrogen. This is in agreement with observations made by Londry and Suflita [2], who found that thiols inhibited methanogenesis at concentrations above 5 mM. They tested the toxicity of a mixture of long-chain (C5-C8) and cyclic thiols with lactate as the substrate.…”
Section: Toxicity Of Thiols On Methanogenesissupporting
confidence: 92%
See 1 more Smart Citation
“…Our research showed that 50% inhibition of methanogenesis by methanethiol took place at concentrations between 7 and 10 mM for the substrates methanol, acetate, and hydrogen. This is in agreement with observations made by Londry and Suflita [2], who found that thiols inhibited methanogenesis at concentrations above 5 mM. They tested the toxicity of a mixture of long-chain (C5-C8) and cyclic thiols with lactate as the substrate.…”
Section: Toxicity Of Thiols On Methanogenesissupporting
confidence: 92%
“…In addition to inorganic sulfur species (e.g., sulfide, sulfate, sulfite, and thiosulfate), more than 200 sulfurcontaining organic compounds have been identified in crude oils. These include sulfides, thiols, thiophenes, substituted benzo-and dibenzothiophenes, and more complex molecules [2,3]. In this paper, we focus on the anaerobic degradation and toxicity of some short-chain volatile (organic) sulfur compounds that are present in wastewater streams of refineries (e.g., as a result of the extraction of liquefied petroleum gas).…”
Section: Introductionmentioning
confidence: 99%
“…Th e pH levels observed in the four treatments never dropped below approximately 7, and it therefore does not appear likely that pH alone could cause signifi cant inhibition or delay in methane production. Accumulation of volatile organic S compounds such as MT could be toxic to methanogens (Londry and Sufl ita, 1998;van Leerdam et al, 2006), but in this study MT concentrations were generally below toxic levels. Wang et al (2009) observed an inhibition of methane production at 12 mmol L −1 propionic acid, a level also reached in the present study.…”
Section: Cycling Of Volatile Sulfur Compoundsmentioning
confidence: 56%
“…In addition to the inorganic sulfur species, such as elemental sulfur, sulfate, sulfite, thiosulfate, and sulfide, more than 200 sulfurcontaining organic compounds have been identified in crude oils. These include sulfides, thiols, thiophenes, substituted benzo-and dibenzothiophenes, and many considerably more complex molecules (Londry andSuflita, 1998, andMonticello andFinnerty, 1985).…”
Section: Introductionmentioning
confidence: 99%